BLOOD, HONOUR AND STATUS IN ODYSSEY 11*. (16th April 2014) - Martin, Bridget
<x content-type="archive" xml:space="preserve">Abstract</x> During the necromantic ceremony in Odyssey 11 Odysseus slits the throats of two sheep and then proceeds to drain their blood into the βόθρος, or pit, which he has dug in the ground (Od. 11.35–6). At this point in the ceremony the dead swarm up from the Underworld, displaying an innate attraction to the blood (Od. 11.36–7). Such is the overwhelming response of the dead that Odysseus must draw his sword in order to hold back the multitudes who clamour to drink the offering (Od. 11.48–50). Odysseus refuses to allow the dead to approach the blood until Tiresias has drunk the offering and offered a prophecy for the future (Od. 11.95–6). After Tiresias has concluded his prophecy for Odysseus some of the other dead step forward and drink the blood, but to what end? Odysseus does not seek prophecies from these figures, nor do they produce any, which means that their reason for desiring and drinking the blood must lie elsewhere.